Le revival qui « revient » - Giovanni Giuriati (In Situ)
Ethnomusicological literature, in addressing the question of folk music revival, devotes little attention to a relevant phenomenon; that is, both the research of ethnomusicologists and performances of revival have had significant repercussions in the contexts we can call "of origin". We can therefore reflect today, in the logic of an ethnology of the present without regrets for a distant past, on the interactions that music in the oral tradition has had and has still nowadays, at a local level, with urban and popular music (including revival). And consider the influence that the Italian revivalist movement has had on certain repertoires of oral tradition in southern Italy.The article takes the case of Montemarano's tarantella as an example. This music played by clarinet, accordion and frame drum had a strong impact on the Italian revivalist movement, which conferred it an iconic role. Because of the special attention paid by ethnomusicologists, this tarantella (both music and dance) is very popular among those who have taken an interest in Italian popular music and was widely performed in folk revival settings. The study suggests five elements that show the effect that, at the local level, has the music of folk-revival on the transformations of this music for Carnival, which still functions in Montemarano to support and order the feast: the multiplication of instrumentalists, the impact of professionalization, the use of ciaramella, the production of CDs, the issue of copyright.